Optimización del proceso de sellado en la producción de yogurt griego en la industria láctea del grupo Rossi” - Sánchez Cedeño, Mauricio José (2024)
The main activity of the dairy company “GRUPO ROSSI” is the production of milk products based on Italian manufacturing processes; this company is located in the city of Machachi. This degree project research focuses on the optimization of the Greek yogurt sealing process. We centered on this area of the company because its processes are not meeting the objectives determined by the company. Therefore, the research project aims to determine the current conditions of the process through field research; in addition, a mixed research was carried out which is supported by qualitative and quantitative approaches. Qualitative research stands out for collecting information, such as observations, surveys or content analysis, in order to inquire into meanings, perceptions, experiences and behaviors. For this reason, activities such as the development of the layout, process mapping, surveys and the determination of the problems that occur in the Greek yogurt sealing process were carried out. On the other hand, quantitative research focuses on the collection, analysis of numerical data with the purpose of generalizing discoveries based on representative samples, performing statistical analyzes, and obtaining results that can be objectively measured and compared. Due to this the use of analytical coursegrams, study of times and movements, statistical methods were used to carry out tasks for the determination of the time used in the sealing process. This process takes 3.94 minutes per unit, and then the current efficiency and productivity were established. In addition, it was determined that this process has a current efficiency of 79% with a productivity of 2440 units per month. Based on all this information collected, for this type of process an improvement proposal is developed, in which it was proposed to merge certain activities. In addition, a new analytical coursegram is presented, which was used for a few days to take new samples. For this proposal, a new time per unit was established which is 3.37 minutes per unit, so that the future efficiency would reach a value of 84% and the future productivity with a value of 2760 units per month.